PENGUATAN KOMPETENSI GURU ISMUBA DALAM PEMBELAJARAN AL-QUR’AN (STUDI KASUS DI SD MUHAMMADIYAH KUTOARJO) - Iyus Herdiana Saputra; Tri Ermayani; Rofiq Nurhadi; Fina (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The aim of this research is to describe strengthening the competence of ISMUBA teachers in learning the Koran. This research is a type of qualitative research with a case study method. To obtain research data, data collection techniques were carried out, where this technique has three stages, namely, observation, interviews, and documentation. The data analysis techniques used are data reduction, data analysis and data verification. The results of this research are that strengthening the competence of ISMUBA teachers in learning the Koran at SD Muhammadiyah Kutoarjo is carried out by (1) Organizing training and workshops (2) Carrying out ongoing mentoring and coaching (3) Collaborating with experts and educational institutions (4 ) Carrying out the empowerment of various learning resources and teaching methods (5) Increasing understanding of technology in learning (6) Carrying out evaluation and reflection on learning.